Hubungan Career Anxiety dengan Academic Anxiety pada Mahasiswa - Nazala Khalila Syah; Salwa Nurfaizah; Lucky Purwantini (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
Emerging adulthood requires university students to achieve academic success while simultaneously preparing for their future careers, making them vulnerable to experiencing both academic anxiety and career anxiety. The high unemployment rate among university graduates and the uncertainty of the labor market in Indonesia further emphasize the importance of examining the relationship between these two forms of anxiety, as studies specifically investigating their association remain limited. This study aimed to examine the relationship between career anxiety and academic anxiety among university students in Indonesia. A quantitative correlational design was employed involving 1,062 active diploma and undergraduate students aged 18–26 years from 23 provinces and 73 cities in Indonesia, selected through convenience sampling. Data were collected using the Academic Anxiety Scale (AAS) and the Career Anxiety Scale (CAS). Because the data were neither normally distributed nor linearly related, they were analyzed using the Spearman's rho non-parametric correlation test. The findings revealed a weak positive relationship between career anxiety and academic anxiety (r = 0.224, p = 0,000 <0.05).